Estimation of Elastic Moduli of Particulate Composites by New Models and Comparison with Moduli Measured by Tension, Dynamic, and Ultrasonic Tests. (22nd June 2010) - Bourkas, G.; Prassianakis, I.; Kytopoulos, V.; Sideridis, E.; Younis, C.
Abstract : The elastic constants of particulate composites are evaluated employing a theoretical cube-within-cube formation. Two new models of four and five components, respectively, formed by geometrical combination of three-component models existing in the literature, are used as Representative Volume Elements. Using the governing stress and strain equations of the proposed models, two new equations providing the static elastic and shear moduli of particulate composites are formulated. In order to obtain the dynamic elastic and shear moduli, the correspondence principle was applied successively to components connected in series and/or in parallel. The results estimated by the proposed models were compared with values evaluated from existing formulae in the literature, as well as with values obtained by tensile, dynamic, and ultrasonic experiments in epoxy/iron particulate composites. They were found to be close to values obtained by static and dynamic measurements and enough lower compared with values obtained from ultrasonic experiments. The latter is attributed to the high frequency of ultrasonics. Since measurements from ultrasonic's and from dynamic experiments depend on the frequency, the modulus of elasticity estimated by ultrasonic's is compared with that (storage modulus) estimated by dynamic experiments.